Artificial Intellegence of Financial - Suyono, Suyono (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Artificial intelligence (AI) is receiving increasing attention in business and society. In banking, the first applications of AI were successful; however, AI is primarily applied in investment banking and customer contactless backend services. AI in commercial banking with its focus on customer interaction has received little attention so far. Introducing AI in commercial banking can change business processes and interactions with customers, which can create research opportunities for behavioral finance. Based on this research center, we conducted a structured literature review to identify the application of AI in commercial banks and the opposition to the application of AI. Our findings show that by using AI, commercial banks can reduce loan losses, improve security in processing payments, automate compliance-related work, and improve customer targeting. Researchers are concerned about realizing technological advantage; embedding AI in business processes; ensuring user acceptance through transparency; personal; and the appropriate bag. Finally, we propose a research agenda for financial behavior. The global financial system is currently at a new stage of its development, which is marked by the introduction of information and communication technologies in all areas of finance. They enable the improvement of business processes and enterprise management and service delivery processes, as they enable organizations to receive more information about their customers and consumers, therefore, to provide better financial services that meet customer requirements